(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge, attitudes and practices of parent’ s autism. Subjects and methods: Cross-sectional study with 220 parents, who have a child with autism participate in survey at the National Hospital of Acupuncture in 2025. Results: Regarding knowledge about autism, 60% of parents knew the definition of autism, 43.18% of parents recognized typical symptoms, but only 17.27% clearly understood the causes of autism. Regarding the attitudes of parents with autistic children, 48.64% parents were worried when thinking about their children’s future, but they have a positive outlook, believing in the value of early intervention and opportunities for social integration for their children (52.73% and 52.27% of parents are proud to see their children’s progress. Regarding parents’ practices towards autistic children, they proactively support their children in basic activities: 76.82% of parents help their children participate in outdoor activities, 51.82% of parents guide their children to use support tools such as toothbrushes and mouthwash cups, but there are still limitation in accessing specialized support services (23.64%) and community connections (35.91%). Conclusion: It is necessary to further improve the understanding of parents with autistic children about knowledge, attitudes and practices to have appropiate behavior, contributing to improving the effectiveness of interventions for autistic children.